2017
DOI: 10.3916/c52-2017-06
|View full text |Cite
|
Sign up to set email alerts
|

M-learning and augmented reality: A review of the scientific literature on the WoS repository

Abstract: La realidad aumentada surge como un útil sobre el que se precisa examinar su real implementación educativa. Esta investigación hace un análisis bibliométrico sobre documentos del repositorio Web of Science. Este servicio ofrece en Internet la producción científica de más de 7.000 instituciones de todo el mundo. Se toma como base un universo de 12.000 revistas indexadas y 148.000 actas de conferencias y se selecciona una muestra centrada en los términos «m-learning» y «augmented reality» como descriptores o com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 52 publications
2
21
0
13
Order By: Relevance
“…Only, a continuity has been found between "usability" and "instruction" that is repeated in both periods. These results are consistent with those other studies that have found there to be a great variety of research, highlighting the conceptualization of this phenomenon, the development of new RA methodologies, motivation and the attitude, special relocation, academic achievement, and the subjects in which the RA is studied [32,38].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Only, a continuity has been found between "usability" and "instruction" that is repeated in both periods. These results are consistent with those other studies that have found there to be a great variety of research, highlighting the conceptualization of this phenomenon, the development of new RA methodologies, motivation and the attitude, special relocation, academic achievement, and the subjects in which the RA is studied [32,38].…”
Section: Discussionsupporting
confidence: 91%
“…These benefits favor both the improvement of teaching results and the environment of training spaces [29].There has not been a significant number of articles reporting on AR. The main findings of related research have focused on quantifying their scientific productions [30], new technological trends analyzed by researchers [31], and the changes and advances produced by this type of teaching approach [32]. Other studies have focused on the country (Spain) and the time period (2015-2017) for greater scientific production [33].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Todos estos elementos, positivos y negativos, convergen en que empleada de manera eficaz, el interés por los contenidos curriculares aumenta (Di Serio, Ibañez y Delgado, 2013;Estepa y Nadolny, 2015;Fombona, Pascual-Sevillano y González-Videgaray, 2017;Marín, 2016;Marín-Díaz, 2017;Moreno, Leiva y Matas, 2017;Cabero Almenara, Vázquez Cano y López Meneses, 2018), de ahí que un elemento clave para ello sea la motivación que tanto docentes como estudiantes han de tener para imbricarse en su utilización. De este modo, se puede contemplar que los profesores serán los que despierten la curiosidad en los alumnos tanto por la ampliación de los contenidos enseñados en el aula, como por el uso de la RA no solo en el momento del aprendizaje, sino también en su vida fuera del centro educativo.…”
unclassified
“…Ορισμένες από τις δυνατότητες που προσφέρει η κινητή μάθηση, σύμφωνα με τους Fombona, Pascual-Sevillana and González-Videgaray, είναι μια διευρυμένη και πολύπλευρη πρόσβαση σε πληροφορίες, που συνδυάζει υπερβατικές καινοτομίες, όπως άτυπες και παιγνιώδεις δραστηριότητες, εικονική πραγματικότητα (Virtual Reality), η συμμετοχή σε διαδικτυακές ομάδες προβληματισμού, και διευρυμένα δίκτυα συνεργατικής αλληλεπίδρασης με σκοπό την υλοποίηση συγκεκριμένων Projects. (Fombona, et. al.…”
Section: η καινοτομία της πλατφόρμας ε-Liosunclassified